The role of adjuvants in regional anesthesia: the postoperative analgesic effectiveness of dexamethasone vs. tramadol given as adjuvants to bupivacaine for ultrasound-guided supraclavicular block for upper extremity surgery—a prospective cohort study - Tadesse, Haregewoin; Sintayhu, Ashagrie; Dendir, Getahun; Tila, Mebratu; Habtu, Elias; Alemu, Afewerk; Alemayehu, Mihiretu (Frontiers in Anesthesiology, 2024)
Background: Brachial plexus block is used as surgical anesthesia and analgesia for postoperative pain.Recently, the use of local anesthetics for regional nerve block has been enhanced by mixing with a different class of drugs as adjuvants. These adjuvants of local anesthetics improved the quality and duration of nerve block and reduced the dose-dependent side effects of local anesthetics. However, the effectiveness of these adjuvants varies depending on the nature of the nerve block and the type of local anesthetics used. Therefore, we aimed to compare the postoperative analgesic effectiveness of dexamethasone versus tramadol when used as an adjuvant to bupivacaine for ultrasound guided supraclavicular block in upper extremity surgery.Methods: Utilizing a prospective cohort study design a total of consecutive 126 patients who were undergoing upper extremity surgery with ultrasound guided supraclavicular block were included. Patients were divided in to three groups based on the preference of the responsible anesthetist to use adjuvants with bupivacaine for the block. Dexamethasone group (n=42), given 30ml of 0.25% bupivacaine with 8 mg dexamethasone, tramadol group (n=42), given 30ml of 0.25% bupivacaine with 100mg tramadol and nonadjuvant group (n=42) given 30ml of 0.25% bupivacaine alone. Result: A total of 126 patients were recruited and analyzed. There is no statistical difference in demographic data among groups. The postoperative NRS score was significantly reduced in the dexamethasone and tramadol group compared to the non-adjuvant group with a value of p <0.001. NRS score in dexamethasone group at 18hr and 24hrwas statistically much lower than in tramadol and nonadjuvant group. The postoperative duration of analgesia was significantly prolonged in the dexamethasone (1069±316.99 minutes) group than tramadol group (617.02±214.05 minutes) and non-adjuvant group (434.17±111.23 minutes) with a value of p <0.001. Patients in non-adjuvant group had significantly higher total analgesic consumption over 24 hours. The dexamethasone group experienced significantly less incidence of nausea, with no differences in other complications among the groups.Addition of dexamethasone as adjuvants to bupivacaine for ultrasound-guided supraclavicular block improve postoperative analgesia. We recommended the integration of dexamethasone as an adjuvant to local anesthetics during nerve blocks to enhance postoperative pain management after surgery.